Sub-ambient heat exchanger network design including compressors. (1st December 2015) - Fu, Chao; Gundersen, Truls
Abstract: Heat can be converted into work and vice versa, and this fact provides opportunities for the integration between them. This paper presents a systematic methodology for the integration of compressors into heat exchanger networks below ambient temperature. The objective is to minimize exergy consumption. Four theorems are proposed and used as the basis for the design methodology. Pinch Compression, i.e., compression starts at pinch temperature, is proven to be preferred under certain conditions. It is concluded that minimum exergy consumption can be achieved when compression starts at pinch temperatures, ambient temperature or the cold utility temperature. Highlights: The integration of heat and work is studied. Compressors are integrated with sub-ambient heat exchanger networks. Pinch Compression is proven to be preferred. The exergy consumption is minimized.